Short-Term Nutritional Support for Infants With Unrestricted Ventricular Septal Defects to Promote Postoperative Recovery - Zhang, Qi-Liang; Lin, Shi-Hao; Lin, Wen-Hao; Cao, Hua; Chen, Qiang (Frontiers in Pediatrics, 2022)
Objective: This study aims to explore the effect of short-term nutritional support for infants with unrestricted ventricular septal defects on improving preoperative nutritional status and promoting postoperative recovery. Methods: The clinical data of 35 infants with unrestricted ventricular septal defects who were treated with two weeks of nutritional support in our hospital from December 2020 to March 2021 were analysed retrospectively. The clinical data of 38 infants with unrestricted ventricular septal defects who were treated in our hospital from May 2020 to October 2020 were selected as controls. Results: The preoperative body weight, preoperative albumin, preoperative prealbumin and preoperative haemoglobin in the intervention group were significantly higher than those in the control group (p<0.05). The postoperative ventilator time, intensive care time and discharge time in the intervention group were significantly shorter than those in the control group (p<0.05). Conclusion: Performing two weeks of nutritional support for infants with unrestricted ventricular septal defects can improve their preoperative nutritional status and promote postoperative recovery.